Ergot Alkaloids (Re)generate New Leads as Antiparasitics. - John D Chan; Prince N Agbedanu; Thomas Grab; Mostafa Zamanian; Peter I Dosa; Timothy A Day; Jonathan S Marchant (Public Library of Science (PLoS), 2015)
Praziquantel (PZQ) is a key therapy for treatment of parasitic flatworm infections of humans and livestock, but the mechanism of action of this drug is unresolved. Resolving PZQ-engaged targets and effectors is important for identifying new druggable pathways that may yield novel antiparasitic agents. Here we use functional, genetic and pharmacological approaches to reveal that serotonergic signals antagonize PZQ action in vivo. Exogenous 5-hydroxytryptamine (5-HT) rescued PZQ-evoked polarity and mobility defects in free-living planarian flatworms. In contrast, knockdown of a prevalently expressed planarian 5-HT receptor potentiated or phenocopied PZQ action in different functional assays. Subsequent screening of serotonergic ligands revealed that several ergot alkaloids possessed broad efficacy at modulating regenerative outcomes and the mobility of both free living and parasitic flatworms. Ergot alkaloids that phenocopied PZQ in regenerative assays to cause bipolar regeneration exhibited structural modifications consistent with serotonergic blockade. These data suggest that serotonergic activation blocks PZQ action in vivo, while serotonergic antagonists phenocopy PZQ action. Importantly these studies identify the ergot alkaloid scaffold as a promising structural framework for designing potent agents targeting parasitic bioaminergic G protein coupled receptors.